THE EFFICIENCY OF BLENDED LEARNING IN TEACHING THE ENGLISH LANGUAGE TO STUDENTS OF NON-LINGUISTIC SPECIALTIES - Kartseva, Elena; Tavberidze, Daria (Revista Inclusiones, 2020)
The authors analyze the implementation of the blended learning approach to teaching the English language to students of non-linguistic specialties. It is shown that the use of blended learning in the modern learning environment entails the utilization of educational resources. These resources enable one to simultaneously use the advantages of classroom-based learning and the benefits of distance learning technologies. Based on students’ questionnaires, the authors determine students’ attitudes towards the implementation of a blended learning approach during English language classes. In the study, the survey method is used to collect and analyze information that reflects the opinions of students of non-linguistic specialties towards studying the English language with the implementation of a blended learning approach. The survey of students of humanities specialties has indicated certain disadvantages to using the blended learning approach. At the same time, the results of the study have shown that blended learning also has some advantages. A conclusion has been made that the implementation of the blended learning approach in teaching the English language leads to increased efficiency of the education process.